Work Notifications and Work-Life Balance: What TPS Supervisors Experienced in the 2024 Elections? - Sutopo, Arya Budi (Klabat Journal of Management, 2025)
The 2024 simultaneous regional elections involve various stakeholders in the oversight process, including Polling Station Supervisors or Tempat Pemungutan Suara (TPS) supervisors. However, the high workload caused by constant work notifications can affect the balance between work and personal life (work-life balance). This study aims to analyze the impact of work notifications on the work-life balance of TPS supervisors in Bruno District. Using a quantitative approach, data was collected through questionnaires completed by 94 TPS supervisors. A simple linear regression analysis was conducted to identify the relationship between the intensity of work notifications and the level of work-life balance. The results indicate that work notifications have a significant impact on work-life balance, with higher notification frequency contributing to a decline in life balance. This study provides valuable insights for election organizers in designing a more humane work system to improve the well-being of TPS supervisors. These findings are expected to serve as a foundation for more effective policymaking to support the sustainability of the electoral system in the future.